Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a question which Kind of makes me crazy right now. If I have the equation $1=\ln(2•3)$, I could then use the e function to remove the $\ln.$ Doing that I get $e^1 = 6.$ Now say we are using the rules of the log at the beginning we could write $$1 = \ln(2)+\ln(3).$$ Using the $e$ function I get $e^1 = 2+3$. How is this possible? What is my mistake?

share|cite|improve this question
up vote 4 down vote accepted

Your mistake is that $e^{\ln 2+\ln 3} = e^{\ln2} \cdot e^{\ln3}$ and not $e^{\ln 2+\ln 3} = e^{\ln2} + e^{\ln3}$.

share|cite|improve this answer

You can't have the equation like $1 = \log(2\cdot 3)$. It's like saying if you have $2= 3$ and if I add $1$ on both sides then to get $3=4$. Now can I ask how $3=4$?

Moreover if $1 = \log{2} + \log{3}$, then $e^{1} = e^{\log{2}+\log{3}} = e^{\log{2}} \cdot e^{\log{3}} = 2 \cdot 3=6$

share|cite|improve this answer
3  
That's not the major mistake. – Hendrik Vogt Jul 3 '11 at 13:02
    
@Hendrik: Thanks. Yes, I think, I have done it correctly now. – user9413 Jul 3 '11 at 13:04

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.